Feasibility study of ultrasound video bronchoscopy for sampling endobronchial lesions. (22nd March 2020) - Oki, Masahide; Saka, Hideo; Kogure, Yoshihito; Oka, Saori; Nakahata, Masashi; Shigematsu, Fumie; Ishida, Akane; Kitagawa, Chiyoe
Abstract: Introduction: Endobronchial biopsy using forceps is generally performed with a standard bronchoscope, while a needle is used with an endobronchial ultrasound (EBUS) bronchoscope. An EBUS video bronchoscope, such as the EB‐530US instrument (Fujifilm, Tokyo, Japan), provides good visibility and may, therefore, enable both forceps biopsies and needle aspirations to be performed. Objectives: The aim of this study was to investigate the feasibility of performing forceps biopsies and needle aspirations using the EBUS video bronchoscope for diagnosing endobronchial lesions. Methods: Seventy patients with suspected endobronchial lesions based on a computed tomography scan were recruited and underwent forceps biopsy using the EB‐530US EBUS bronchoscope. If the result of a rapid on‐site cytological evaluation was negative, an additional needle aspiration of the same lesion or other target lesions was performed. The primary outcome was the completion rate of bronchoscopy, using only the EBUS bronchoscope without removal. Results: In the 70 patients, forceps biopsies and/or needle aspirations using the EBUS video bronchoscope were performed and completed without removing the EBUS bronchoscope in 67 patients (95.7%). The remaining three patients required the removal of the EBUS bronchoscope from the trachea (blood clot obstruction of the working channel in one patient and change to a thin bronchoscope to sample an EBUS bronchoscope‐inaccessible lesion in two others). The EBUS bronchoscope provided diagnostic material in 66 patients (94.3%). One case each of bleeding and pneumonia were observed (1.4%). Conclusion: Both forceps biopsy and needle aspiration are feasible using a Fujifilm EB‐530US EBUS video bronchoscope.